Analysis of the Elimination of Strict Liability in the Omnibus Law on Massive Deforestation in Indonesia and its Effect on Global Warming and Climate Change - Khoirunnisa, Khoirunnisa; Jubaidi, Didi (Universitas 17 Agustus 1945 Jakarta, 2025)
The Job Creation Law or omnibus law passed in 2020 has caused controversy among the public and legal experts. One aspect that has attracted attention is the elimination of corporations as parties that can be held criminally liable. Previously, corporations could be convicted if they were involved in environmental crimes. However, with the adoption of Omnibus Law, corporate criminal liability has been abolished, except in cases of environmental crimes that result in human death. The elimination of Strict Liability in the Omnibus Law against perpetrators of Massive Deforestation in Indonesia can have a major effect on global warming and climate change. This article analyzes the impact of the elimination of corporate liability in criminal acts and the importance of considering the balance between economic interests and social justice. The purpose of this research is to find out how the impact of the elimination of the principle of strict liability in the criminal act of forest destruction passed in 2020 on Global Warming and Climate Change. This research uses a normative juridical approach, with a literature study that includes various sources such as scientific writings or articles in the form of books, online media, dissertations or other literature. The elimination of the principle of strict liability in the omnibus law has affected massive deforestation in Indonesia closely related to environmental protection and maintenance. Without strict liability, proving fault or negligence in deforestation cases becomes more. the elimination of strict liability for corporate criminal liability in cases of massive deforestation in Indonesia can have significant implications for global warming and climate change. It may reduce deterrence, make it harder to hold corporations accountable, and hinder efforts to protect the environment.